STRATEGI PENYALURAN PUPUK BERSUBSIDI DI INDONESIA - Ragimun, Ragimun; Makmun, Makmun; Setiawan, Sigit (JURNAL ILMIAH M-PROGRESS, 2020)
o realize food self-sufficiency in Indonesia, it needs to be supported by effective distribution of subsidizedfertilizer. The main causes of ineffective distribution of subsidized fertilizers are irregularities, weak oversightfrom implementing institutions and weak community control. Likewise, the aspects of transparency andinformation disclosure in the chain of subsidized fertilizer implementation are also still weak. So far, theregulations governing the mechanism for implementing subsidized fertilizer distribution policies are quiteadequate but their implementation is still weak. In this study a descriptive approach is used to explore anddescribe the development of distribution as well as the strategies adopted to obtain more effective alternativedistribution of subsidized fertilizer. This study also compares the policy of distribution of subsidized fertilizersin several countries. Based on the results of the study, several schemes or alternative distribution of subsidizedfertilizer are still needed in Indonesia. Irregularities occur because of errors in the collection of data "RDKK", the distribution of subsidized fertilizers to unauthorized parties, the large volume of distribution, procurementand distribution of subsidized fertilizers as well as the obstacles in calculating fertilizer subsidies. Onerecommendation that can be submitted for the distribution of subsidized fertilizers effectively is that severalalternative channels can be implemented. One alternative for the distribution of subsidized fertilizers includesthe use of an electric card through "Gapoktan", distribution of fertilizer subsidies through the use of the PupukIndonesia Mart kiosk and through direct distribution to fertilizer producers in Indonesia.Keywords: fertilizer subsidy policy, distribution scheme, food self-sufficiency